Integration of the Values of Surah Al-‘Alaq in the Development of Human Resource Managerial Capacity - Fatmawati Sungkawaningrum; Fatmah Watty Pelupes; Muhammad Hakimi Mohd Shafiai (ZAD Al-Mufassirin, 2026)
This study is motivated by the urgency of strengthening human resource managerial capacity in addressing economic disparities and limited financial access within the informal business sector. It proposes the integration of values derived from Surah Al-‘Alaq (verses 1–5) as a foundational framework for developing managerial capacity that is not only technically rational but also ethically grounded and sustainable. This study aims to examine the relevance and contribution of these values to the development of human resource managerial capacity among micro and small business actors. A qualitative research approach was employed, utilizing normative analysis of Qur’anic texts combined with empirical insights into socio-economic behavior. The findings indicate that the values of literacy (iqra’), knowledge-seeking, and an ethical work orientation embedded in Surah Al-‘Alaq significantly contribute to the development of adaptive managerial practices, improved financial awareness, and enhanced human resource capacity. However, challenges such as a weak transformational mindset and opportunistic economic behavior remain constraints in capacity development. This study concludes that the integration of Qur’anic values provides a strategic and ethical framework for strengthening human resource managerial capacity in micro and small enterprises.